2016
DOI: 10.1136/bjophthalmol-2016-309298
|View full text |Cite
|
Sign up to set email alerts
|

First-line intra-arterial versus intravenous chemotherapy in unilateral sporadic group D retinoblastoma: evidence of better visual outcomes, ocular survival and shorter time to success with intra-arterial delivery from retrospective review of 20 years of treatment

Abstract: PurposeThe introduction of intra-arterial chemotherapy (IAC) as salvage treatment has improved the prognosis for eye conservation in group D retinoblastoma. The aim of this study was to compare the outcomes of consecutive patients with advanced unilateral disease treated with either first-line intravenous chemotherapy (IVC) or first-line IAC.DesignThis is a retrospective mono-centric comparative review of consecutive patients.PatientsSporadic unilateral retinoblastoma group D cases treated conservatively at Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 46 publications
6
83
0
Order By: Relevance
“…Using systemic chemotherapy alone, approximately half (48%) of Group D eyes were salvaged in this series, which is consistent with previous reports of Group D eyes treated with primary intravenous chemotherapy . Several recent studies have documented significantly higher globe salvage rates for Group D eyes treated with intraarterial chemotherapy . Salvage rates in Group D eyes using intraarterial chemotherapy has been reported to range from 68 to 90% with several factors including subretinal and vitreous seeding playing a significant role in relapse .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Using systemic chemotherapy alone, approximately half (48%) of Group D eyes were salvaged in this series, which is consistent with previous reports of Group D eyes treated with primary intravenous chemotherapy . Several recent studies have documented significantly higher globe salvage rates for Group D eyes treated with intraarterial chemotherapy . Salvage rates in Group D eyes using intraarterial chemotherapy has been reported to range from 68 to 90% with several factors including subretinal and vitreous seeding playing a significant role in relapse .…”
Section: Discussionsupporting
confidence: 88%
“…8,10 Several recent studies have documented significantly higher globe salvage rates for Group D eyes treated with intraarterial chemotherapy. 12,13 Salvage rates in Group D eyes using intraarterial chemotherapy has been reported to range from 68 to 90% with several factors including subretinal and vitreous seeding playing a significant role in relapse. 6,16,[44][45][46] The results of our retrospective study suggest that the success rate for Group D eyes following intravenous chemotherapy can now be augmented in the era of intravitreal melphalan injections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual outcomes are seldom reported for eyes treated with OAC or intravitreous chemotherapy. Even though visual acuity, on average, in our population was encouraging compared to patients treated with unilateral retinoblastoma, an evaluation reporting visual outcomes in greater detail should be undertaken to arrive at definitive conclusions. Our results in group D eyes need to be improved despite the advances seen with the use of OAC.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the common indications for IAC in retinoblastoma patients include unilateral retinoblastoma that cannot be halted by local treatments alone (e.g., cryotherapy or laser photocoagulation) and advanced unilateral retinoblastoma (such as group D and E based on the ICRB) [30]. Several studies had previously reported the following advantages of using IAC in patients with group D retinoblastoma: better eye conservation rates and greater visual acuity compared to systemic chemotherapy, shorter treatment period and ability to repeat the therapy several times using multiple agents without endangering the patients' life and vision [28,38]. It is also noteworthy to mention that IAC can save naïve eyes with advanced retinoblastoma from enucleation particularly when subretinal seeding is present (2 year ocular survival rate of 83%) [39].…”
Section: Indicationsmentioning
confidence: 99%